Captivity causes taxonomic and functional convergence of gut microbial communities in bats - Xiao,Yanhong; Xiao,Guohong; Liu,Heng; Zhao,Xin; Sun,Congnan; Tan,Xiao; Sun,Keping; Liu,Sen; Feng,Jiang (PeerJ, 2019)
Background Diet plays a crucial role in sculpting microbial communities. Similar diets appear to drive convergence of gut microbial communities between host species. Captivity usually provides an identical diet and environment to different animal species that normally have similar diets. Whether different species’ microbial gut communities can be homogenized by a uniform diet in captivity remains unclear. Methods In this study, we compared gut microbial communities of three insectivorous bat species (Rhinolophus ferrumequinum, Vespertilio sinensis, and Hipposideros armiger) in captivity and in the wild using 16S rDNA sequencing. In captivity, R. ferrumequinum and V. sinensis were fed yellow mealworms, while H. armiger was fed giant mealworms to rule out the impact of an identical environment on the species’ gut microbial communities. Results We found that the microbial communities of the bat species we studied clustered by species in the wild, while the microbial communities of R. ferrumequinum and V. sinensis in captivity clustered together. All microbial functions found in captive V. sinensis were shared by R. ferrumequinum. Moreover, the relative abundances of all metabolism related KEGG pathways did not significantly differ between captive R. ferrumequinum and V. sinensis; however, the relative abundance of “Glycan Biosynthesis and Metabolism” differed significantly between wild R. ferrumequinum and V. sinensis. Conclusion Our results suggest that consuming identical diets while in captivity tends to homogenize the gut microbial communities among bat species. This study further highlights the importance of diet in shaping animal gut microbiotas.
Keywords: Diet; Microbiome; Convergence; Bat